The Role of Religion in Policies of Legal Village-Owned Enterprises to Improve the Economic Rights of Village Communities - Ferricha, Dian (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
In the context of village development in Indonesia, BUM Desa is an important instrument for enhancing the economic welfare of village communities. However, many villages have not fully utilized the potential of BUM Desa due to the lack of integration between religious values and economic policies. Therefore, this study seeks to explore how the application of religious principles can influence BUM Desa policies and contribute to improving the economic rights of village communities. Data collection techniques included in-depth interviews with BUM Desa administrators, village officials, and local religious figures in several villages that have implemented religious-based policies in BUM Desa management and participatory observation, while data analysis was carried out through content analysis and thematic analysis methods to identify key themes in the data. The importance of understanding the relationship between religion and economic policies at the village level, especially in the context of BUM Desa, which have the potential to be the driving force of the local economy. This study involve how religious principles can be integrated into the legal framework for managing BUM Desa to ensure that the economic rights of village communities are fulfilled fairly and sustainably. This study shows that the integration of religious values into BUM Desa policies has significant potential to improve the economic rights of village communities. By prioritizing the principles of justice, shared welfare, and social responsibility rooted in religious teachings, BUM Desa can be more effective in achieving its economic and social goals. This study provides important insights for village policymakers in formulating inclusive and sustainable strategies to advance the village economy.